Tracing stakeholder terminology then and now: Convergence and new pathways. (4th September 2017) - Griffin, Jennifer J.
Abstract : Over the past four decades, stakeholder research has united a chorus of voices from different disciplines using different terminology for different audiences all related to a seemingly similar topic: those that affect and are affected by business. By juxtaposing a comprehensive review of the early years of stakeholder research against more recent stakeholder research, we identify areas of common convergence (a focus on relationships and Freeman's definition of a stakeholder) as well as emergent scholarship (mechanisms underlying stakeholder relationships and solutions‐oriented impacts). We develop an organizing framework consisting of three stakeholder‐related themes: who or what is a stakeholder; mechanisms underlying stakeholder relationships; and outcomes‐oriented stakeholder research. Future research opportunities include: simultaneously examining multiple stakeholders at multiple levels; multiplier effects along the value chain and across geographies; and net impacts (examining whether net positive benefits inclusive of negative outcomes exist). We conclude by identifying how stakeholder research can "move the needle" on important business issues such as: income inequality and CEO pay; human rights and building community inclusion; disease alleviation; and food security in firms' continuous quest to create value.